Reconciliation of Machine-Human Relations Through Ikigai Robotics: A Review - Bin Ramlan, Muhammad Nadzif (Japanese Department Faculty of Cultural Science Universitas 17 Agustus 1945 Surabaya, 2024)
New dynamics in interactions between humans and machines have been generated as a result of the rapid advancement of artificial intelligence (AI) and robotics, which has significantly impacted human existence. In order to improve the interaction between humans and robots, this paper investigates the incorporation of the Japanese concept of Ikigai, or